The simplification of the expression will be as follows:
(a^7b^8)/(a^4b^4)
According to the rules of indices, when you divide numbers with the same base, it's the same as subtracting their powers. Hence we shall have:
(a^7b^8)/(a^4b^4)
=(a^(7-4))(b^(8-4))
=a^3b^4
the answer is a^3b^4
Mika placed $4200 in a savings account which compounds interest continuously at a rate of 2.3%.
How much will she have in the account after 3 years?
1st year 4200 x 1.023 = 4296.60
2nd year 4296.60 x 1.023 = 4395.4218
3rd year 4395.4218 x 1.023 = 4496.5165
Round to the nearest dollar.
$4497
Answer:
This is khan academy. I am pretty sure they have a video for this but whatever.
Step-by-step explanation:
So we are using sin, cosine, and tan. 3.4 is the hypotenuse. the side is X. The angle is 20 degrees. So, this is adjacent to hypotenuse. This means it is cosine.
3.4cos(20)= around 3.19
And thats that! let me know if this is wrong and I will try to fix it.
An even function can be reflected about the y axis and map onto itself
example: y=x^2
an odd function can be reflected about the origin and map onto itself
example: y=x^3
a simple test is the following
if f(x) is even then f(-x)=f(x)
if f(x) is odd then f(-x)=-f(x)
so
even function
subsitute -x for each and see if we get the same function
remember to fully expand these
g(x)=(x-1)^2+1=x^2-2x+1+1=x^2-2x+2 is the original one
g(x)=(x-1)^2+1
g(-x)=(-x-1)^2+1
g(-x)=(1)(x+1)^2+1
g(-x)=x^2+2x+1+1
g(-x)=x^2+2x+2
not same because the original has -2x
not even
g(x)=2x^2+1
g(-x)=2(-x)^2+1
g(-x)=2x^2+1
same, it's even
g(x)=4x+2
g(-x)=4(-x)+2
g(-x)=-4x+2
not the same, not even
g(x)=2x
g(-x)=2(-x)
g(-x)=-2x
not same, not even
g(x)=2x²+1 is the even function